Effectiveness of measles, mumps and rubella vaccine as immunotherapeutic agent for cutaneous viral warts - Wahengbam, Anupama Devi; Jeevan, Jeyakumari; Dogiparthi, Sowmya (International Journal of Research in Dermatology, 2020)
Immunotherapy for management of cutaneous wart with measles, mumps and rubella vaccine (MMR) is a promising new modality of management. Evaluation of the same has been done by various studies over the years reporting its effectiveness. A literature search was done using PubMed and google scholar. This short narrative review documents the response rates in various clinical studies done till 2019 which have reported the efficacy of MMR vaccine as an immunotherapeutic agent which ranged from 26-84% graded as complete response which is complete clearance of the treated warts. These studies were performed for evaluating MMR vaccine as single agent or done in comparison with other therapeutic agents. The broad range of responses points to a need of doing further clinical studies which will substantiate the effectiveness of MMR vaccine in the treatment of cutaneous warts.